Microeconometric Analysis of the Retirement Decision Italy - Miniaci, Raffaele (OECD Economics Department Working Papers, 1998)
This paper exploits an Italian microeconomic data set to study retirement behaviour of women and men using survival analysis techniques. After a brief introduction to the Italian pension system and to the Bank of Italy survey, different specifications of a Cox proportional hazard model are estimated. These show clearly that younger generations retire earlier, more educated and self-employed workers retire later, and women tend to postpone exit from the labour force beyond the standard entitlement age. The timing of retirement is inelastic to replacement rates: a 20% reduction of the replacement rate would cause a delay of 2-6 months ...